Dampak Perubahan Kebijakan Pengadaan Secara Elektronik melalui E-Katalog V5 Menjadi V6 bagi Penyedia di Kecamatan Balongbendo - Prasetyo Dwi Pangesti Adji; Sri Kamariyah; Zainal Fatah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the implementation of procurement of goods and services through e-Catalog version 6 in Balongbendo District after the enactment of policy changes from the previous version (V5). In addition, this study also identifies impacts, obstacles, and strategies to increase system effectiveness. This study uses a qualitative descriptive method with a document study approach based on the Electronic Procurement of Goods/Services Implementation Report for the third quarter of 2025 as a secondary data source. The results of this study show that the implementation of the V6 e-Catalog has been relatively effective with a completion rate of 87.18% of a total of 39 procurement packages. However, obstacles were found in the form of human error (75%) and system bugs (25%) that caused some packages to be unable to be processed. The transition from version 5 to version 6 brings a positive impact in terms of increased transparency and efficiency, but it also poses new challenges in adapting to the latest version. This study confirms that the success of digital transformation of public procurement does not only depend on technological aspects, but also on human readiness and adaptive institutional governance.